Predictors of surgical complications in boys with hypospadias: data from an international registry - Scougall, Kathryn (2023)
Background: Complications are frequently reported after hypospadias repair and there is a need to understand the factors that influence their occurrence. Methods: Data from boys with hypospadias born between 2000 and 2020 were obtained from the International Disorders of Sex Development (I-DSD) Registry. Logistic regressions, fisher’s exact tests and spearman’s correlation tests were performed on the data to assess associations between clinical factors and complication rates. Results: Of the 551 eligible boys, data were available on 160 (29%). Within the cohort, the median (range) External Masculinization Score (EMS) was 6 (2, 9). All presented with one or more additional genital malformation and 61 (38%) presented with additional extragenital malformations. Disorders of androgen action, androgen synthesis and gonadal development were diagnosed in 28 (18%), 22 (14%) and 9 (6%) boys, respectively. The remaining 101 (62%) patients were diagnosed as having non-specific 46,XY Disorders of Sex Development. Eighty (50%) boys had evidence of abnormal biochemistry, and gene variants were identified in 42 (26%). Median age at first hypospadias surgery was 2 years (0, 9), and median length of follow-up was 5 years (0, 17). Postsurgical complications were noted in 102 (64%) boys. There were no significant associations with postsurgical complications. Conclusions: Boys with proximal hypospadias in the I-DSD Registry have high rates of additional comorbidities and a high risk of postoperative complications. No clinical factors were significantly associated with complication rates. High complication rates with no observable cause suggest the involvement of other factors which need investigation.